2016
DOI: 10.1590/0034-737x201663030008
|View full text |Cite
|
Sign up to set email alerts
|

Chemical thinning affects yield and return flowering in 'Jubileu' peach

Abstract: Peach hand thinning improves fruit quality; however, it requires a high demand of labor and increases production costs. The objective of this study was to evaluate the effect of growth regulators applied at post-flowering as an alternative to hand thinning of peaches. The experiment was conducted with peach cultivar Jubileu, in 2012. The treatments consisted of no thinning, hand thinning 45 days after full bloom (DAFB), ethephon (85 and 120 mg L-1), benzyladenine (BA) (400 mg L-1), and BA plus gibberellic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Peach tree cultivars exhibit high bloom, a fact that results in an excessive number of fruits which is incompatible with the production capacity of the plant (Giovanaz et al, 2016;Barreto et al, 2018). The excessive number of fruits leads to small fruits that have low commercial value (Giovanaz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peach tree cultivars exhibit high bloom, a fact that results in an excessive number of fruits which is incompatible with the production capacity of the plant (Giovanaz et al, 2016;Barreto et al, 2018). The excessive number of fruits leads to small fruits that have low commercial value (Giovanaz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Peach tree cultivars exhibit high bloom, a fact that results in an excessive number of fruits which is incompatible with the production capacity of the plant (Giovanaz et al, 2016;Barreto et al, 2018). The excessive number of fruits leads to small fruits that have low commercial value (Giovanaz et al, 2016). In order to improve the quality of fruits and increase their commercial value, thinning must be carried out in the orchard (Greene & Costa, 2013;Turk et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower number of fruits in the plant enables production of fruits with a higher mean mass due to the increased availability and allocation of nutrients to each fruiting organ (GIOVANAZ et al, 2016). VEGO et al (2010) reported that a decrease in the number of fruits reduced competition for carbohydrates, thereby, improving the distribution of assimilates resulting in fruits with larger mass, diameter, and length.…”
Section: Resultsmentioning
confidence: 99%
“…Thinning technique aims to remove excess fruitlets from the trees to increase the fruit size, color and quality. Thinning also helps to minimize or eliminate alternate bearing and branch breaking, while decreasing the number of defective fruits and minimizing harvesting costs (GIOVANAZ et al, 2016). SOUZA et al (2013SOUZA et al ( , 2017 reported that some peach cultivars develop alternate production, with variable yield over consecutive years, which may be minimized by adopting methods that regulate the fruit load of peach trees.…”
Section: Introductionmentioning
confidence: 99%